Pulmonary Actinomycosis Mimicking Pulmonary Aspergilloma and a Brief Review of the Literature - Higashi, Yoshitsugu (Intern Med, 2017)
Pulmonary actinomycosis is a rare pulmonary infection that often exhibits unspecific symptoms and radiological findings. We herein report a case of pulmonary actinomycosis that mimicked pulmonary aspergilloma in an immunocompetent patient.